Use of Botulinum Toxin in the Treatment of Patients with Upper Limb Spasticity After Stroke – a Systematic Review - Małgorzata Gucwa; Beata Bednarz-Tomczyk (Rehabilitacja Medyczna)
Introduction: Botulinum toxin neurolysis is a common pharmacological intervention used to alleviate the consequences of spasticity. The aim of this study was to conduct a systematic review of the literature to assess the efficacy of botulinum neurotoxin type A (BoNT-A) in the treatment of patients with upper limb spasticity following stroke.Material and methods: Electronic databases were searched: PubMed, Google Scholar and Scopus, taking the literature from 2015-2025 into account. The keywords used were: stroke, BoNT-A, spasticity and upper limb. Available publications were searched according to the established inclusion and exclusion criteria, ultimately analysing four articles.Results: In the analysed studies, the obtained results differed according to treatment protocol. The measurement of upper limb motor functions using the Fugl-Meyer Assessment (FMA) scale showed improvement in each of the studied groups.Conclusions: The use of BoNT-A in the treatment of patients with upper limb spasticity after stroke has a beneficial effect on improving limb function and reducing spasticity. Further studies and analyses are needed to assess the actual contribution of BoNT-A to improving upper limb function following stroke.